A System for Real-Time 3D Neurosurgical Planning - Goble, John C.; Snell, John W.; Hinckley, Ken; Katz, William T.; Kassell, Neal F. (Proc. SPIE 2359, Visualization in Biomedical Computing 1994, 1994)
We see two major barriers which limit clinical use of 3D surgical planning software. First, images must be automatically segmented. Second, the planning software must be easy for physicians to use. We describe a prototype system which addresses these problems, making computerguided neurosurgical planning feasible in the real world.